Respuesta :

Answer:

The simplified expression is  5+(-3)(6x-5)=2(10-9x)

Step-by-step explanation:

Given expression is 5+(-3)(6x-5)

    To simplify the given expression :

    5+(-3)(6x-5)=5+((-3)(6x)-(-3)(5))   ( using the distributive property multiply each term to the each term in the factor )

    =5+(-18x+15)

    =5-18x+15

    =-18x+20  ( adding the like terms )

    =20-18x  (rewritting the expression )

    =2(10-9x) ( taking common term 2 outside the factor )

Therefore the simplified expression is 5+(-3)(6x-5)=2(10-9x)